2021
DOI: 10.1039/d1tb00895a
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized and decellularized bone extracellular matrix-incorporated electrospun nanofibrous scaffold for bone regeneration

Abstract: The extracellular matrix (ECM)-based materials has been employed as scaffolds for bone tissue engineering, providing a suitable microenvironment that possesses biophysical and biochemical cues for cell attachment, proliferation and differentiation....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 58 publications
7
28
0
Order By: Relevance
“…When the diameter of fibers is reduced to the nanometer range, it endows the electrospun nanofibers with several favorable properties, including high surface area to volume ratio, numerous nano-sized pores and high size uniformity, which highly mimic the structure of the ECM. 11,12 It is known that a nano-structured ECM directly interacts with cells and acts as an active depot that regulates the activity of growth factors. 13 Therefore, the biomimetic features of electrospun nanofibers can play a critical role in facilitating cell growth and guiding tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…When the diameter of fibers is reduced to the nanometer range, it endows the electrospun nanofibers with several favorable properties, including high surface area to volume ratio, numerous nano-sized pores and high size uniformity, which highly mimic the structure of the ECM. 11,12 It is known that a nano-structured ECM directly interacts with cells and acts as an active depot that regulates the activity of growth factors. 13 Therefore, the biomimetic features of electrospun nanofibers can play a critical role in facilitating cell growth and guiding tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that the in ammation reaction caused by scaffold should be resolved within 14 days, and chronic in ammation could result in an infection [51] . It has been proven that PCL exhibited good biocompatibility and widely used as a safe biomaterial in BTE led [52,53] . In this study, in order to ensure the biocompatibility of the PCL/dB-ECM nano brous scaffolds, we must rst prepare dB-ECM effectively and safely.…”
Section: Discussionmentioning
confidence: 99%
“…By repopulating cells in these acellular scaffolds, multiple studies have demonstrated the reformation of cell-enriched tissues and their therapeutic potential. Bone-derived ECM scaffolds combined with n-poly (e-caprolactone) nanofibers promoted the attachment, migration, proliferation, and osteogenic differentiation of rat MSCs [ 110 ]. Subsequent transplantation to a rat calvarial critical-size defect model mitigated the foreign body reaction and facilitated bone regeneration.…”
Section: Applications Of Ecm Scaffolds From Other Sources In Tissue E...mentioning
confidence: 99%